Model Pengembangan Supervisi - Murtando, Murtando (DIMAR: Jurnal Pendidikan Islam, 2024)
In the world of education, academic supervision is an inseparable part of efforts to improve the quality of learning and the quality of school administration. Sohertian emphasized that educational supervision or educational supervision is more than providing services to educational stakeholders, especially teachers who are good individually and in groups, but in supervision there are efforts to improve the quality of learning processes and outcomes. Apart from that, the focus in supervision includes: (1) student achievement, (2) quality of student services at school, (3) school leadership and management. The first and second focuses are academic supervision work and the third focus is the task of managerial supervision. With good educational supervision, the quality of education will be maintained and continue to improve. In Law of the Republic of Indonesia number 14 of 2005 concerning Teachers and Lecturers, it is explained about the competencies that a teacher must possess, namely including pedagogical competence, personality competence, social and professional competence. Through professional education, these four competences are interrelated. Meanwhile, Law No. 14 of 2005 concerning Teachers and Lecturers in the explanatory chapter of article 10 paragraph (1) states that what is meant by pedagogical competence is the ability to manage student learning activities. Furthermore, in the Explanatory Chapter of Article 28 paragraph 3 of PP 19 of 2005 concerning SNP, what is meant by pedagogical competence is the ability to manage student learning which includes: (1) Mastering student characteristics, both physical, spiritual, social, cultural, emotional and intellectual. (2) Mastering learning theories and educational learning principles. (3) Develop a curriculum related to whose subjects are taught. (4) Organizing educational learning. (5) Utilizing information and communication technology for one's own benefit while studying. (6) Facilitate the development of students' potential to actualize various potentials. (7) Communicate effectively, empathetically and politely with students. (8) Carrying out assessments and evaluations of learning processes and outcomes. (9) Utilize the results of assessments and evaluations for learning purposes. (10) Carry out reflective actions to improve the quality of learning.